Enantioselective adsorption on chiral ceramics with medium entropy - Chao Chen; Yinglin Ma; Kunda Yao; Qingmin Ji; Wei Liu (Nature Communications)
Abstract Chiral metal surfaces provide an environment for enantioselective adsorption in various processes such as asymmetric catalysis, chiral recognition, and separation. However, they often suffer from limitations such as reduced enantioselectivity caused by kink coalescence and atomic roughness. Here, we present an approach using medium-entropy ceramic (MEC), specifically (CrMoTa)Si2 with a C40 hexagonal crystal structure, which overcomes the trade-off between thermal stability and enantioselectivity. Experimental confirmation is provided by employing quartz crystal microbalance (QCM), where the electrode is coated with MEC films using non-reactive magnetron sputtering technology. The chiral nature is verified through transmission electron microscopy and circular dichroism. Density-functional theory (DFT) calculations show that the stability of MEC films is significantly higher than that of high-index Cu surfaces. Through a combination of high-throughput DFT calculations and theoretical modeling, we demonstrate the high enantioselectivity (42% e.e.) of the chiral MEC for serine, a prototype molecule for studying enantioselective adsorption. The QCM results show that the adsorption amount of L-serine is 1.58 times higher than that of D-serine within a concentration range of 0-60 mM. These findings demonstrate the potential application of MECs in chiral recognition.